Calorie Restriction Does Not Increase Short-term or Long-term Protein Synthesis - Miller, Benjamin F. (Oxford University Press, 2013)
Increased protein synthesis is proposed as a mechanism of life-span extension during caloric restriction (CR). We hypothesized that CR does not increase protein synthesis in all tissues and protein fractions and that any increased protein synthesis with CR would be due to an increased anabolic effect of feeding. We used short- (4 hours) and long-term (6 weeks) methods to measure in vivo protein synthesis in lifelong ad libitum (AL) and CR mice. We did not detect an acute effect of feeding on protein synthesis while liver mitochondrial protein synthesis was lower in CR mice versus AL mice. Mammalian target of rapamycin (mTOR) signaling was repressed in liver and heart from CR mice indicative of energetic stress and suppression of growth. Our main findings were that CR did not increase rates of mixed protein synthesis over the long term or in response to acute feeding, and protein synthesis was maintained despite decreased mTOR signaling.